Ekspresigen Homeobox Protein A (HOXA) 10 pada Jaringan Endometrium Penderita Endometriosis yang Infertil - Johan Ricardo; Henry Salim; Muhammad Rusda; Letta Lintang; Edi Ardiansyah; Hanudse Hartono (Majalah Kedokteran Nusantara The Journal Of Medical School, 2015)
Introduction :Endometriosis is associated with the abnormality of estrogen and progesterone.Both estrogen and progesterone had a role as strong mitogene in endometrialfocus.One of the mitogene is HOXA10 which was expressed in the nucleus of glandular and stromalcells. Method :This is an analytic study with cross sectionalapproach.40 subjects who fulfilled the inclusion criteria were obtained. lmmunohistochemistry was then performed to evaluate HOXA10 expression.This study was performed from March to April 2015.The obtained data was then analyzed statistically.This study objective is to determine HOXA1O gene expression in endometrialtissue of infertile women with endometriosis Result :Majority of subjects from endometriosis group were fromthe age group of 31-40 years old with 13 subjects (65o/o) and nulliparous with 19 subjects (95%).While from non endometriosis group, majority of subjects were from the age group 41-50 years old with 15 subjects (75%) and parity of 1-3 with 11 subjects (55%). Based on HOXA10 expression intensity, 14 subjects (70%) showed no expression, expression of +1 with 6 subjects (30°/o).While from non endometriosis group, expression of +3 were found in 13 subjects (65o/o), and expression of +2 were found in 7 subjects (35°/o), p<0.05.Conclusion : There is a significant difference of HOXA10 gene expression in endometrialtissue of subject with endometriosis and without endometriosis. Keywords :HOXA10, endometriosis, infertility